Malaysian Politics under Mahathir - Milne, Diane K. Mauzy (Routledge, 1999)
Malaysia's long-serving Prime Minister, Mahathir Mohamad, is a controversial political figure. High rates of economic growth and a strikinf reduction in poverty have been the hallmarks of a vibrant "Tiger" economy.